2023
DOI: 10.1002/oto2.40
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Perceptions of Canadian Otolaryngology‐Head and Neck Surgeons and Residents on Environmental Sustainability

Abstract: Objective Healthcare systems, specifically operating rooms, significantly contribute to greenhouse gas emissions. Addressing operating room environmental sustainability requires understanding current practices, opinions, and barriers. This is the first study assessing the attitudes and perceptions of otolaryngologists on environmental sustainability. Study Design Cross‐sectional virtual survey. Setting Email survey to active members of the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…One study (5%) mentioned barriers relating to incentives. This survey found that the most common barriers to environmental sustainability in OTs were ‘lack of incentives’ 69 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…One study (5%) mentioned barriers relating to incentives. This survey found that the most common barriers to environmental sustainability in OTs were ‘lack of incentives’ 69 .…”
Section: Resultsmentioning
confidence: 96%
“…Often, studies did not differentiate between roles when reporting determinants of behaviour. Many studies did not report the specific role or specialty of the participants; of those that did, eight involved anaesthetists and associated healthcare workers 60 , 62 , 66 , 67 , 73 , 75 , 78 , 80 , and one study for each of the specialties of cataract related healthcare 63 , obstetrics and gynaecology 77 , ear nose and throat 69 , and ophthalmology 64 . A further study reported the department of each participant, with 11 specialties included, such as vascular surgery, trauma and orthopaedics, and plastic surgery 70 .…”
Section: Resultsmentioning
confidence: 99%
“…). These leaders possess an unwavering commitment to sustainability and rmly believe in promoting ecofriendly practices (Hathi et al, 2023).…”
Section: Ghrm With Gip With Mediating Role Of Ekmentioning
confidence: 99%
“…Despite some progress in related studies, the area remains relatively unexplored. A study conducted by the Department of Otolaryngology-Head and Neck Surgery at LHSC found that Canadian otolaryngologists strongly believe in climate change, but there was some ambivalence surrounding ORs being a strong contributor [10]. Other studies found varied barriers, such as lack of support from leadership and inadequate knowledge or education [11,12].…”
Section: Introductionmentioning
confidence: 99%